Pelatihan penggunaan Canva bagi guru guna meningkatkan kualitas pembelajaran di SMP Katolik Don Bosco Semboro, Kabupaten Jember - Fadilla Purwitasari; Ricky Angga Ariska; Sarah Yuliarini (Nur Science Institute, 2026)
Creating engaging teaching materials is an essential aspect of the learning process. However, this isn't easy to achieve in the field at present, including at Don Bosco Catholic Junior High School in Semboro. One reason is that the academic community struggles to obtain engaging teaching materials. One way to solve this problem is by designing teaching materials. To solve this problem, the community service team proposed providing Canva usage training for the academic community of Don Bosco Catholic Junior High School in Semboro. This training is conducted using the demonstration method. The first step was to provide detailed instructions for accessing Canva accounts and using its various features. The next step was to have participants practice using Canva to create engaging teaching materials. The results of this training using the demonstration method show that participants were able to produce engaging teaching materials in Canva by the end of the training.